Exploiting Chemical Protein Synthesis to Study the Role of Tyrosine Sulfation on Anticoagulants from Hematophagous Organisms - Correa, Clara Bersi Motta [UNESP]; Kogawa, Ana Carolina; Chorilli, Marlus [UNESP]; Salgado, Herida Regina Nunes [UNESP] (Amer Chemical Soc, 2023)
Tyrosine sulfation is a post-translational modification (PTM) that modulates function by mediating key protein-protein interactions. One of the early proteins shown to possess this PTM was hirudin, produced in the salivary glands of the medicinal leech Hirudo medicinalis, whereby tyrosine sulfation led to a similar to 10-fold improvement in a- thrombin inhibitory activity. Outside of this pioneering discovery, the involvement of tyrosine sulfation in modulating the activity of salivary proteins from other hematophagous organisms was unknown. We hypothesized that the intrinsic instability of the tyrosine sulfate functionality, particularly under the acidic conditions used to isolate and analyze peptides and proteins, has led to poor detection during the isolation and/or expression of these molecules.Herein, we summarize our efforts to interrogate the functional role of tyrosine sulfation in the thrombin inhibitory and anticoagulant activity of salivary peptides and proteins from a range of different blood feeding organisms, including leeches, ticks, mosquitoes, and flies. Specifically, we have harnessed synthetic chemistry to efficiently generate homogeneously sulfated peptides and proteins for detailed structure-function studies both in vitro and in vivo.Our studies began with the leech protein hirudin P6 (from Hirudinaria manillensis), which is both sulfated on tyrosine and O- glycosylated at a nearby threonine residue. Synthetically, this was achieved through solid-phase peptide synthesis (SPPS) with a late -stage on-resin sulfation, followed by native chemical ligation and a folding step to generate six differentially modified variants of hirudin P6 to assess the functional interplay between O-glycosylation and tyrosine sulfation. A one-pot, kinetically controlled ligation of three peptide fragments was used to assemble homogeneously sulfoforms of madanin-1 and chimadanin from the tick Haemaphysalis longicornis. Dual tyrosine sulfation at two distinct sites was shown to increase the thrombin inhibitory activity by up to 3 orders of magnitude through a novel interaction with exosite II of thrombin. The diselenide-selenoester ligation developed by our lab provided us with a means to rapidly assemble a library of different sulfated tick anticoagulant proteins: the andersonins, hyalomins, madanin-like proteins, and hemeathrins, thus enabling the generation of key structure-activity data on this family of proteins. We have also confirmed the presence of tyrosine sulfation in the anticoagulant proteins of Anopheles mosquitoes (anophelins) and the Tsetse fly (TTI) via insect expression and mass spectrometric analysis. These molecules were subsequently synthesized and assessed for thrombin inhibitory and anticoagulant activity. Activity was significantly improved by the addition of tyrosine sulfate modifications and led to molecules with potent antithrombotic activity in an in vivo murine thrombosis model. The Account concludes with our most recent work on the design of trivalent hybrids that tandemly occupy the active site and both exosites (I and II) of a-thrombin, with a TTI-anophelin hybrid (K-i = 20 fM against a-thrombin) being one of the most potent protease inhibitors and anticoagulants ever generated. Taken together, this Account highlights the importance of the tyrosine sulfate post-translational modification within salivary proteins from blood feeding organisms for enhancing anticoagulant activity. This work lays the foundation for exploiting native or engineered variants as therapeutic leads for thrombotic disorders in the future.